Influence of CO2 emission rates on the stability of the thermohaline circulation - Stocker, Thomas F.; Schmittner, Andreas (Nature, 1997)
Present estimates of the future oceanic uptake of anthropogenic CO2 and calculations of CO2-emission scenarios (ref 1) are based on the assumption that the natural carbon cycle is in steady state. But it iswell known from palaeoclimate records (ref 2,3,4,5) and modelling studies (ref 6,7,8,9) that the climate system has more than one equilibrium state, and that perturbations can trigger transitions between them. Anticipated future changes in today's climate system due to human activities have the potential to weaken the thermohaline circulation of the North Atlantic Ocean (ref 10,11,12), which would greatly modify estimates of future oceanic CO2 uptake (ref 13). Here we use a simple coupled atmosphere–ocean climate model to show that the Atlantic thermohaline circulation is not only sensitive to the final atmospheric CO2 concentration attained, but also depends on the rate of change of the CO2 concentration in the atmosphere. A modelled increase to 750 parts per million by volume (p.p.m.v.) CO2 within 100 years (corresponding approximately to a continuation of today's growth rate) leads to a permanent shut-down of the thermohaline circulation. If the final atmospheric concentration of 750 p.p.m.v. CO2 is attained more slowly, the thermohaline circulation simply slows down. The reason for this rate-sensitive response of the climate system lies with the transfer of buoyancy in the form of heat and fresh water from the uppermost layers of the ocean into the deep waters below. This sensitivity of the simulated thermohaline circulation to the rate of change of atmospheric CO2 concentration has potentially important implications for the choice of future CO2-emission scenarios (ref 1).